Risk factors for renal dysfunction in the postoperative course of liver transplant. - Lebrón-Gallardo, Miguel; Herrera-Gutiérrez, Manuel Enrique; Seller Pérez, Gemma Luisa; Curiel Balsera, Emilio; Fernández-Ortega, Juan F.; Quesada García, Guillermo (The American Association for the Study of Liver Diseases, 2004)
Renal dysfunction (RD) is a frequent complication after orthotopic liver transplantation (OLT), and it has an unfavorable effect on the prognosis of OLT patients. The purpose of our study was to identify possible risk factors for RD and its impact on survival. The possible relations of pre-, peri-, and postoperative variables to early-onset renal dysfunction (ED) (within the 1st 3 months), late-onset renal dysfunction (LD) (between 3 and 6 months), and chronic renal dysfunction (CRD) (beyond 6 months) was analyzed. We studied 245 liver transplants in 241 patients. RD was found in 64.1% of these patients, and 69% of the patients with RD recovered. LD was found in 16.7% of the transplant patients. In the multivariate analysis, baseline serum creatinine, perioperative volume of transfused bank-red blood cells, Acute Physiology and Chronic Health Evaluation (APACHE) II score at intensive care unit (ICU) admission, and infection were associated with the development of RD. Overall mortality was 27.8% and for the RD group, it was 33.5%. LD, but not ED, was related to lower survival (together with graft dysfunction and APACHE II score at ICU admission). In conclusion, ED is frequent alter OLT and is related to preexisting RD, the volume of transfused bank--red blood cells during surgery, higher APACHE II score at ICU admission, and infection. In general, the prognosis for ED is good, in contrast with that of LD, which is associated with diminished survival.
https://openpolicyfinder.jisc.ac.uk/id/publication/15949?from=single_hit
Keywords: Hígado - Trasplante; Riñones - Enfermedades - Factores de riesgo; Liver trasplantation; Renal insuficiency; Risk factors